2012
DOI: 10.1017/s000711451200075x
|View full text |Cite
|
Sign up to set email alerts
|

The anti-proliferative effect of TI1B, a major Bowman–Birk isoinhibitor from pea (Pisum sativumL.), on HT29 colon cancer cells is mediated through protease inhibition

Abstract: Bowman -Birk inhibitors (BBI) from legumes, such as soyabean, pea, lentil and chickpea, are naturally occurring plant protease inhibitors which have potential health-promoting properties within the mammalian gastrointestinal tract. BBI can survive both acidic conditions and the action of proteolytic enzymes within the stomach and small intestine, permitting significant amounts to reach the large intestine in active form to exert their reported anti-carcinogenic and anti-inflammatory properties. In a previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 32 publications
1
39
0
2
Order By: Relevance
“…Many of those naturally found PIs were further characterized from different plant species which mainly included trypsin from serine protease group which have been tested for various diseases (Richardson, 1991; Tamir et al, 1996; Majumdar, 2013). This review explains about PIs of all earlier reported plant species that have been used as therapeutic agents and tested against different diseases and human disorders (Table 1; Murugesan et al, 2001; Neuhof et al, 2003; Troncoso et al, 2003; Kobayashi et al, 2004; Lanza et al, 2004; Clemente et al, 2005, 2012; Kim et al, 2005; Suzuki et al, 2005; Capaldi et al, 2007; Banerjee et al, 2008; Tochi et al, 2008; Caccialupi et al, 2010; Hsieh et al, 2010; Joanitti et al, 2010; García-Gasca et al, 2012; Magee et al, 2012; de Paula et al, 2012a; Borodin et al, 2013; Ferreira et al, 2013; Rakashanda et al, 2013b; Clemente and Arques, 2014; Souza et al, 2014) and future scope to search for new species, which are as follows:…”
Section: Roles Of Plant Protease Inhibitors In Health and Disease Conmentioning
confidence: 99%
“…Many of those naturally found PIs were further characterized from different plant species which mainly included trypsin from serine protease group which have been tested for various diseases (Richardson, 1991; Tamir et al, 1996; Majumdar, 2013). This review explains about PIs of all earlier reported plant species that have been used as therapeutic agents and tested against different diseases and human disorders (Table 1; Murugesan et al, 2001; Neuhof et al, 2003; Troncoso et al, 2003; Kobayashi et al, 2004; Lanza et al, 2004; Clemente et al, 2005, 2012; Kim et al, 2005; Suzuki et al, 2005; Capaldi et al, 2007; Banerjee et al, 2008; Tochi et al, 2008; Caccialupi et al, 2010; Hsieh et al, 2010; Joanitti et al, 2010; García-Gasca et al, 2012; Magee et al, 2012; de Paula et al, 2012a; Borodin et al, 2013; Ferreira et al, 2013; Rakashanda et al, 2013b; Clemente and Arques, 2014; Souza et al, 2014) and future scope to search for new species, which are as follows:…”
Section: Roles Of Plant Protease Inhibitors In Health and Disease Conmentioning
confidence: 99%
“…IC 50 values suggest that NCIH322 lung cancer cells are strongly inhibited by both inhibitors at lower concentrations in comparison to other cell lines. Their pharmacological effects may be mediated through inhibition of the protease activity and the subsequent modulation of the protease pro-survival signaling as LC-pi I and II strongly inhibited the in vitro activity of trypsin, elastase and chymotrypsin (Clemente et al, 2010), also TI1B, a major Bowman-Birk isoinhibitor from pea (Pisum sativum L.) on HT29 colon cancer cells (Clemente et al, 2012) and antitumor Protease Inhibitor from Mini-Black Soybean (Ye and Ng, 2011). These evidences have made the plant protease inhibitors to be considered as neutraceutical proteins, owing to prevention and treatment of cancer (de Mejia and Dia, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the anti-proliferative effect of rTI1B, a major pea isoinhibitor expressed heterologously in Pichia pastoris, has been evaluated using colon cancer cells grown in vitro. Comparisons of the effects of rTI1B with those observed using a related synthetic mutant derivative, showed that the proliferation of HT29 colon cancer cells was inhibited significantly by rTI1B in a dose-dependent manner, whereas the mutant which lacked trypsin and chymotrypsin inhibitory activity did not show any significant effect on colon cancer cell growth (Figure 1) [68]. Although the molecular mechanism(s) of this chemopreventive activity remains unknown, the reported data indicate that both trypsin-and chymotrypsin-like serine proteases involved in carcinogenesis are likely primary targets for BBI.…”
Section: Colorectal Cancermentioning
confidence: 99%